Prenatal MR imaging of congenital diaphragmatic hernias: association of MR fetal lung volume with the need for postnatal prosthetic patch repair - Henzler, Claudia; Zahn, Katrin; Weis, Meike; Weiß, Christel; Schönberg, Stefan; Schaible, Thomas; Büsing, Karen-Anett; Neff, Wolfgang (European radiology, 2015)
Objective: To assess whether the need for postnatal prosthetic patch repair of the diaphragmatic defect in neonates with a congenital diaphragmatic hernia (CDH) is associated with the antenatal measured observed-to-expected magnetic resonance fetal lung volume (o/e MR-FLV). Methods: The o/e MR-FLV was calculated in 247 fetuses with isolated CDH. Logistic regression analysis was used to assess the prognostic value of the individual o/e MR-FLV for association with the need for postnatal patch repair. Results: Seventy-seven percent (77 %) of patients with a CDH (190/247) required prosthetic patch repair and the defect was closed primarily in 23 % (57/247). Patients requiring a patch had a significantly lower o/e MR-FLV (27.7 ± 10.2 %) than patients with primary repair (40.8 ± 13.8 %, p < 0.001, AUC = 0.786). With an o/e MR-FLV of 20 %, 92 % of the patients required patch repair, compared to only 24 % with an o/e MR-FLV of 60 %. The need for a prosthetic patch was further influenced by the fetal liver position (herniation/no herniation) as determined by magnetic resonance imaging (MRI; p < 0.001). Fetal liver position, in addition to the o/e MR-FLV, improves prognostic accuracy (AUC = 0.827). Conclusion: Logistic regression analysis based on the o/e MR-FLV is useful for prenatal estimation of the prosthetic patch requirement in patients with a CDH. In addition to the o/e MR-FLV, the position of the liver as determined by fetal MRI helps improve prognostic accuracy.